Suppression by central adenosine A3 receptors of the cholinergic defense against cardiovascular aberrations of sepsis: role of PI3K/MAPKs/NFκB signaling - El-Naggar, Amany E.; Helmy, Mai M.; El-Gowilly, Sahar M.; El-Mas, Mahmoud M. (Frontiers in Pharmacology, 2024)
Introduction: Despite the established role of peripheral adenosine receptors in sepsis-induced organ dysfunction, little or no data is available on the interaction of central adenosine receptors with sepsis. The current study tested the hypothesis that central adenosine A3 receptors (A3ARs) modulate the cardiovascular aberrations and neuroinflammation triggered by sepsis and their counteraction by the cholinergic antiinflammatory pathway. Methods: Sepsis was induced by cecal ligation and puncture (CLP) in rats pre-instrumented with femoral and intracisternal (i.c.) catheters for hemodynamic monitoring and central drug administration, respectively. Results: The CLP-induced hypotension, reduction in overall heart rate variability (HRV) and sympathovagal imbalance towards parasympathetic predominance were abolished by i.v. nicotine (100 µg/kg) or i.c. VUF5574 (A3AR antagonist, 2 µg/rat). In addition, the selective A3AR agonist, 3-iodobenzyl-5'-N-methylcarboxamidoadenosine IB-MECA, 4 µg/rat, i.c.) exaggerated the hypotension and cardiac autonomic dysfunction induced by sepsis and opposed the favorable nicotine actions against these septic manifestations. Immunohistochemically, IB-MECA abolished the nicotinemediated downregulation of NFκB and NOX2 expression in rostral ventrolateral medullary areas [Type here] 2 (RVLM) of brainstem of septic rats. The inhibitory actions of IB-MECA on nicotine responses disappeared after i.c. administration of PD98059 (MAPK-ERK inhibitor), SP600125 (MAPK-JNK inhibitor) or wortmannin (PI3K inhibitor). Moreover, infliximab (TNFα inhibitor) eliminated the IB-MECA-induced rises in RVLM-NFκB expression and falls in HRV, but not blood pressure. Conclusion: Central PI3K/MAPKs pathway mediates the A3AR counteraction of cholinergic defenses against cardiovascular and neuroinflammatory aberrations in sepsis.